Про визначення центральності за допомогою детекторів протонів, розсіяних вперед - Cieśla, K.; Staszewski, R.; Chwastowski, J. J. (Publishing house "Academperiodika", 2019)
The forward proton detectors, already installed at the Large Hadron Collider, are studied in the context of heavy-ion collisions. The potential of such detectors in measuring the nuclear debris coming from the spectator fragments is presented. The geometric acceptance of the forward proton detectors for different debris is estimated. The impact of experimental conditions and the Fermi motion on the acceptance is studied. A possibility of the collision impact parameter reconstruction from the measurement of nuclear fragments is discussed.